Ectoparasite Prevalences of Grouper Fish (Epinephelus fuscogutatus x Epinephelus polyphekadion) Cultured in Floating Net Cages - Sudirman Adibrata; Muh Yusuf; Cristiana Manullang (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2020)
Monitoring the health of the reared fish in a floating net cage (FNC) is often conducted by examining their ectoparasites. This study determines ectoparasite prevalences of grouper fish (Epinephelus fuscogutatus x E. polyphekadion). It was conducted in the waters surrounding Pongok Island, South Bangka Regency. The health examination of both fish and ectoparasites was carried out by applying simple random sampling during three periods, November 2016 (I), February 2017 (II) and May 2017 (III). Hydro-oceanography surveys were done every month during the three years. The grouper checkings (I, II and III) indicated the prevalences of ectoparasites in these periods were 43.3%, 8.8% and 13.5%, respectively. Fish death highly occurred in the period I, and the grouper survival rate at harvesting time was only 70% from initial seed stocking of 1,500 fish. The ectoparasite intensities during the research periods were 1.6, 1.6 and 1.5, respectively. This condition implies that every 10 groupers would potentially be attacked by at least 15-16 ectoparasites. A slow seawater current flow triggered the quick uplifting of the ectoparasites from the seafloor. The water condition at the FNC location in 2011 and 2017 was still under the quality standard. The ectoparasites were coming from the surrounding environment of the FNC location. It is inevitable that the fish culture management should focus on cleansing the ectoparasites attaching on the groupers, dusting the net cage clean, and arranging the harvest pattern on a particular month following the surrounding environmental condition to prevent ectoparasite attacks.